Sunset in the West: outsourcing editorial work from the UK to India - a case study of the impact on workers. (1st January 2007) - ,; ,
Abstract : This paper presents a case study carried out in a large academic publishing and printing house. Interviews were carried out in both locations with senior and middle management, workers and trade unionsto gain their perspectives on the outsourcing of typesetting and editorial work from the UK to India. In Britain, 'working in publishing' traditionally represented a prestigious and highly sought-after career for graduates with high skills, both generic and occupation-specific. This paper explores the shock experienced by these workers when faced with the prospect of losing their jobs to the Indian labour market and argues that the outsourcing of skilled work in an increasingly globalised labour market introduces new forms of precariousness even to highly qualified workers with diverse skills. However the study also finds that the workers in India who are taking over these tasks are not experiencing the benefits previously enjoyed by their British counterparts. On the contrary, on the evidence of this case study, their jobs too are highly insecure. It concludes that the qualitative effects of offshore outsourcing on employment are more important than quantitative impacts.